ANALGESIC AND ANTI-INFLAMMATORY ACTIVITY OF MONOTERPENOID MYRTENAL IN RODENTS - Stela Dragomanova; Lyubka Tancheva; Marieta Georgieva; Radoslav Klisurov (Peytchinski Publishing, 2019)
Inflammation and pain are common phenomena associated with a number of diseases. The search for new pharmacological agents is an important factor in delivering better therapy. Many plants and their active ingredients monoterpenes exhibit analgesic and anti-inflammatory activity but have not been fully studied. Purpose The bicyclic monoterpenoid Myrtenal (M) is a component of many plants essential oils. Researches on total plant extracts as well as on essential oils reveal a wide range of biological effects with various mechanisms. However, there is no data in the literature about Myrtenal effects in pain and inflammation. Aim of this study is to investigate the M effects in models of pain and inflammation in laboratory rodents. Materials and methods Anti-nociceptive activity of M (30 mg/kg, b. wt., i. p.) was tested in male ICR mice after single and repeated administration on two established experimental pain models - Acetic acid writhing test (antipyretic type analgesia) and Hot plate test (narcotic type analgesia). Anti-inflammatory activity of M (40 mg/kg, b. wt., i. p.) was evaluated on the 24th h from the last treatment after 5-d administration via carrageenan-induced inflammation model on rat paw and was compared with this of the non-steroid anti-inflammatory drug (NSAID) Ketoprofen (2.5 mg/kg, b. wt., i. p.) as a referent. Results In our experiments on Wistar rats and ICR mice M demonstrated significant anti-inflammatory and anti-nociceptive properties (toward both peripheral and thermal pain). In acute administration, significantly decreased the abdominal writhing number at 15th (p < 0.01) and 20th min (p < 0.05) by 47.25 % and by 50.55 % respectively. Myrtenal decreased (p < 0.001) the number of jumps versus control group after repeated treatment - by 40.4 % on 7th and by 43.1 % on the 14th d in comparison to the controls. Conclusions Possible mechanisms are complex, and they probably include sedative and antioxidant properties of Myrtenal.